Konsepsi Pers Islam - Rhoviq, C. (el Harakah: Jurnal Budaya Islam, 1999)
Islam is a religion that can only be conveyed to mankind through "da'wah", and one of the most effective and efficient tools of dakwah in this modern age is the press. As a tool, the Islamic press is necessary and indeed has a foundation, direction and work that can be adequately addressed. The existence and actualization of the concept of the Islamic press implementation is indeed never separated from the process of human life and the environment. In the process that will determine the identity and quality of people in the world historical stage. Carefulness in understanding the times and people as a process, then still able to wrestle the field of the press to seek and find insights development. To such extent not to be easily trapped in saturation, melancholy, decision or erosion of identity and quality as an Islamic press. Islam itu agama yang hanya bisa disampaikan pada umat manusia lewat “dakwah”, dan satu diantara berbagai perangkat dakwah yang efektif dan efisien di zaman mutakhir ini adalah pers. Sebagai suatu perangkat, pers Islami perlu dan memang telah punya landasan, arah dan tatakerja yang secara perspektif dapat disebut memadai. Keberadaan dan aktualisasi konsepsi pers Islam pelaksanaanya memang tak pernah lepas dari proses kehidupan manusia dan lingkungannya. Dalam proses itulah yang akan menentukan identitas dan kualitas umat di pentas kesejarahan dunia. Kejelian dalam memahami zaman dan umat sebagai proses, maka tetap mampu menggeluti bidang pers untuk mencari dan menemukan wawasan pengembangannya. Agar tidak lantas gampang terjebak dalam kejenuhan , kemurungan, keputusan atau erosi identitas dan kualitas sebagai insan pers Islam.